Outcomes of endoscopic sleeve gastroplasty; how does it compare to laparoscopic sleeve gastrectomy? A systematic review and meta-analysis - Mohan, Babu P. (Endosc Int Open, 2020)
Background and study aims  Endoscopic sleeve gastroplasty (ESG) is a novel moderately invasive technique in endo-bariatrics as compared to laparoscopic sleeve gastrectomy (LSG). Data is limited as to its efficacy and safety. Methods  We searched multiple databases from inception through August 2019 to identify studies that reported on ESG in the treatment of obesity. Our goals were to calculate the pooled rates of total weight loss (%TWL), excess weight loss (%EWL), and body mass index (BMI) at 1 month, 6 months, and 12 months with ESG. We included studies that reported on LSG, in a similar time frame as ESG, and compared the 12-month outcomes. Results  From eight studies on ESG (1815 patients), the pooled rates of %TWL at 1 month, 6 months, and 12 months were 8.7 (7.2–10.2), 15.3 (14.1–16.6) and 17.1 (15.1–19.1), respectively. The pooled rates of %EWL at 1 month, 6 months, and 12 months were 31.7 (29.3–34.1), 59.4 (57–61.8) and 63 (51.3–74.6), respectively. The pooled rates of BMI at 1 m, 6 m, and 12 m were 32.6 (31–34.3), 30.4 (29–31.8) and 30 (27.7–32.3, I (2)  = 97), respectively. At 12 months, the pooled %TWL, %EWL and BMI with LSG (7 studies, 2179 patients) were 30.5 (27.4–33.5), 69.3 (60.1–78.4) and 29.3 (27.1–31.4) respectively. On comparison analysis, %TWL with LSG was superior to ESG ( P  = 0.001). %EWL and BMI were comparable. All adverse events, bleeding and gastro-esophageal reflux disease were significantly lower with ESG when compared to LSG. Conclusion  ESG demonstrates acceptable weight loss parameters and seems to have a better safety profile when compared to LSG.